A kind of foam silica gel heat insulation material and its preparation method

CN122878615APending Publication Date: 2026-10-09SUNWAY PRECISION TECHNOLOGY (GUANGDONG) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611077431.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]现有技术中发泡硅胶泡棉因基体导热系数偏高而隔热性能不足;纯气凝胶材料虽导热极低却脆硬无回弹、易掉粉,且需封装或复合使用导致厚度超标;气凝胶与硅胶泡棉的简单共混则面临分散困难、泡孔劣化、力学性能衰减及界面结合弱等系列问题,难以在薄型片材中兼顾低导热与可靠服役性能

Benefits of technology

[0046](1)低导热系数与隔热性能

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of foam silica gel heat insulation materials and preparation method thereof, it is related to silica gel heat insulation material technical field.The application discloses a kind of preparation method of foam silica gel heat insulation material, comprising the following steps: modified vinyl silicone oil, hydroxyl silicone oil, partial alkoxy functionalization hydrogen-containing silicone oil, gas phase white carbon black are blended, obtain A component;Nanoscale deposition hydrophobic modified SiO2 Aerogel powder, amino-terminated functionalized dimethyl silicone oil are blended, obtain aerogel pre-dispersion slurry;A component, aerogel pre-dispersion slurry, dimethyl silicone oil, bubble uniformizing agent, residual alkoxy functionalization hydrogen-containing silicone oil, inhibitor are blended, add deionized water, catalyst blend, obtain foaming glue;Foaming glue calendering forming, vulcanization treatment, obtain foam silica gel heat insulation material;The foam silica gel heat insulation material prepared in the application has low thermal conductivity, good compression resilience, no powder, flame-retardant and thickness controllable in 1.0mm±0.1mm range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of silicone insulation technology, specifically to a foam silicone insulation material and its preparation method. Background Technology

[0002] As 3C electronic products develop towards thinner, lighter, higher-performance, and more integrated designs, the power density of internal heat-generating components such as chips and batteries continues to rise, while the overall thickness of the device is constantly being compressed. The gap between the heat-generating components and the outer casing is typically reduced to 0.5-2.0mm. Within this confined space, it is necessary to prevent heat conduction to the outer casing surface, which could lead to excessively high temperatures in localized hot spots. Simultaneously, it is essential to provide adequate cushioning and vibration damping to protect the precision components. Furthermore, the materials themselves must meet flame-retardant requirements and must not generate dust that could contaminate the circuit boards during long-term use.

[0003] In existing technologies, foamed silicone foam has insufficient thermal insulation performance due to the high thermal conductivity of the matrix; pure aerogel materials, although having extremely low thermal conductivity, are brittle, hard, and lack resilience, and are prone to powdering, and require encapsulation or composite use, resulting in excessive thickness; simple blending of aerogel and silicone foam faces a series of problems such as difficulty in dispersion, cell deterioration, mechanical property degradation, and weak interfacial bonding, making it difficult to achieve both low thermal conductivity and reliable service performance in thin sheets.

[0004] Therefore, developing an aerogel-modified silicone foam with a thickness of about 1.0 mm, low thermal conductivity, good compression resilience, no powder shedding, and flame retardancy has significant industrial application value and urgent market demand. Summary of the Invention

[0005] The purpose of this invention is to provide a foamed silicone thermal insulation material and its preparation method, thereby solving the following technical problems:

[0006] Existing silicone foam cannot simultaneously meet multiple requirements such as heat insulation, cushioning, and flame retardancy.

[0007] The objective of this invention can be achieved through the following technical solutions:

[0008] A method for preparing a foamed silicone thermal insulation material includes the following steps:

[0009] Modified vinyl silicone oil, hydroxyl silicone oil, partially alkoxy-functionalized hydrogen-containing silicone oil, and fumed silica were blended to obtain component A. The blending was carried out by vacuum kneading, and the specific steps were to add the mixture to a kneader and knead it under vacuum at 100-150°C for 2-4 hours.

[0010] Nanoparticle-deposited hydrophobically modified SiO2 aerogel powder and amino-terminated functionalized dimethyl silicone oil were blended to obtain aerogel pre-dispersion slurry;

[0011] Component A, aerogel pre-dispersion slurry, dimethyl silicone oil, foam stabilizer, remaining alkoxy-functionalized hydrogen-containing silicone oil, and inhibitor are blended together, and deionized water and catalyst are added and blended together to obtain foamed adhesive.

[0012] The foamed rubber is calendered and vulcanized to obtain foamed silicone insulation material;

[0013] The nano-deposited hydrophobic modified SiO2 aerogel powder is prepared by hydrophobically treating silica aerogel powder with trimethylchlorosilane and hexamethyldisilazane, and then constructing a nano-active deposition layer on its surface using nano-SiO2 sol solution.

[0014] As a further aspect of the present invention: the dimethyl silicone oil is polydimethylsiloxane with a viscosity of 50-500 mPa·s.

[0015] As a further aspect of the present invention: the foam leveler is a polyether-modified silicone oil foam leveler; the inhibitor is an alkynyl alcohol inhibitor; and the catalyst is a platinum-based catalyst.

[0016] The mass ratio of the amounts of alkoxy-functionalized hydrogen-containing silicone oil added before and after the two additions is 1-3:2-5;

[0017] The foam silicone insulation material comprises the following raw materials in parts by weight: 100 parts by weight of modified vinyl silicone oil, 5-15 parts by weight of hydroxyl silicone oil, 3-8 parts by weight of alkoxy-functionalized hydrogen-containing silicone oil, 5-15 parts by weight of fumed silica, 10-30 parts by weight of nano-deposited hydrophobic modified SiO2 aerogel powder, 4-12 parts by weight of amino-terminated functionalized dimethyl silicone oil, 3-5 parts by weight of dimethyl silicone oil, 1-2.5 parts by weight of foam leveler, 0.05-2 parts by weight of inhibitor, 0.5-3 parts by weight of deionized water, and 0.1-0.5 parts by weight of catalyst.

[0018] As a further aspect of the present invention: the inhibitor is 2-methyl-3-butyn-2-ol or ethynylcyclohexanol; the catalyst is a caster platinum catalyst.

[0019] As a further aspect of the present invention: the vulcanization treatment includes primary vulcanization and secondary vulcanization;

[0020] The primary vulcanization process consists of three stages: the first stage vulcanization temperature is 100-120℃, during which the grafted groups on the aerogel surface undergo a pre-crosslinking reaction with the silicone matrix, establishing interfacial chemical bonds; the second stage vulcanization temperature is 130-150℃, during which hydrogen-containing silicone oil undergoes a hydrosilylation / dehydrogenation reaction with hydroxyl silicone oil / water, and H2 foaming and crosslinking occur simultaneously; the third stage vulcanization temperature is 160-180℃, during which deep crosslinking and shaping occur, and the cell structure is cured; the total vulcanization time for the primary vulcanization is 5-15 minutes.

[0021] The specific steps of secondary vulcanization are as follows: secondary vulcanization at 200-230℃ for 2-4 hours to eliminate residual low molecular weight substances and stabilize the cell structure.

[0022] The thickness of foam silicone insulation material is 0.9-1.1mm.

[0023] As a further embodiment of the present invention, the preparation method of modified vinyl silicone oil includes the following steps: under a nitrogen atmosphere, vinyl silicone oil and isopropanol are added to a reaction flask for dispersion, a catalyst is added, the temperature is controlled at 90-100℃, allyl glycidyl ether is added, the reaction is maintained at this temperature for 2-4 hours, allyl amine is added, the reaction is maintained at this temperature for 2-4 hours, and isopropanol and unreacted monomers are removed by vacuum distillation to obtain modified vinyl silicone oil;

[0024] Vinyl silicone oil has a viscosity of 5000-10000 mPa·s and a vinyl content of 0.16-0.3 wt%.

[0025] The catalyst is a platinum-based catalyst; the addition ratio of vinyl silicone oil, isopropanol, catalyst, allyl glycidyl ether, and allylamine is 100g: 100-200mL: 0.01-0.05g: 2-8g: 1-5g.

[0026] As a further embodiment of the present invention: the preparation method of alkoxy-functionalized hydrogen-containing silicone oil includes the following steps: under a nitrogen atmosphere, hydrogen-containing silicone oil and toluene are added to a reaction flask for dispersion, a catalyst is added, the temperature is controlled at 90-110℃, vinyltriethoxysilane is added, the reaction is kept at the temperature for 4-8 hours, and toluene and unreacted substances are removed by vacuum distillation to obtain alkoxy-functionalized hydrogen-containing silicone oil.

[0027] Hydrogen-containing silicone oil has an active hydrogen content of 0.5-1.0% and a viscosity of 50-150 mm. 2 / s;

[0028] The catalyst is a platinum-based catalyst; the addition ratio of hydrogen-containing silicone oil, toluene, catalyst, and vinyltriethoxysilane is 100g: 100-200mL: 0.02-0.08g: 5-15g.

[0029] As a further aspect of the present invention, the preparation method of amino-terminated modified dimethyl silicone oil includes the following steps:

[0030] Hydroxyl-terminated dimethyl silicone oil and dimethyl silicone oil were added to a reaction flask and dispersed. The temperature was controlled at 60-80℃. Aminoethylaminopropyldimethoxysilane was added and the reaction was maintained at this temperature for 4-6 hours. Methanol was removed by vacuum distillation to obtain amino-terminated modified dimethyl silicone oil.

[0031] The viscosity of hydroxyl-terminated dimethyl silicone oil is 20-40 mm. 2 / s, hydroxyl content 9.0%-9.5%;

[0032] The mass ratio of hydroxyl-terminated dimethyl silicone oil, dimethyl silicone oil, and aminoethylaminopropyl dimethoxysilane is 100:10-30g:5-20g.

[0033] As a further aspect of the present invention, the preparation method of nano-deposited hydrophobically modified SiO2 aerogel powder includes the following steps:

[0034] In a nitrogen atmosphere, silica aerogel powder is added to a closed gas-phase modification reactor and heated to 120-130℃. Trimethylchlorosilane and hexamethyldisilazane are mixed and vaporized. Nitrogen gas is introduced into the gas-phase modification reactor and the reaction is maintained at this temperature for 2-4 hours. The nitrogen gas containing trimethylchlorosilane and hexamethyldisilazane is then stopped. Unreacted trimethylchlorosilane, hexamethyldisilazane and byproducts are removed by purging with nitrogen gas to obtain trimethylsiloxy hydrophobic grafted modified aerogel powder.

[0035] Anhydrous ethanol and deionized water were added to a reaction flask and mixed. Dilute hydrochloric acid was added to adjust the pH of the system to 5.0-5.5. The temperature was controlled at 40-45℃. Tetraethyl orthosilicate was added dropwise. The reaction was kept at the temperature for 3-5 hours under stirring. The temperature was raised to 50-55℃ and kept constant for 1-1.5 hours. The temperature was lowered to room temperature and diluted with anhydrous ethanol to obtain a nano-SiO2 sol solution with a solid content of 11.5-12.5 wt%.

[0036] The trimethylsiloxy hydrophobic grafted modified aerogel powder prepared above was added to a reaction vessel, and the nano-SiO2 sol prepared above was added. The mixture was stirred and deposited at room temperature for 25-35 min, and the temperature was controlled at 55-65℃ for 0.5-1 h. The mixture was then sieved and dried to obtain nano-deposited hydrophobic modified SiO2 aerogel powder.

[0037] As a further aspect of the present invention: the silica aerogel powder has a pore size of 10-50 nm and a specific surface area of ​​200-000 m². 2 / g;

[0038] The mass ratio of silica aerogel powder, trimethylchlorosilane, and hexamethyldisilazane is 100g: 5-15g: 5-15g;

[0039] The dilute hydrochloric acid is a 0.1-0.5 mol / L hydrochloric acid aqueous solution; the addition ratio of anhydrous ethanol, deionized water, and tetraethyl orthosilicate is 180-220 mL: 45-55 mL: 100 g.

[0040] As a further embodiment of the present invention: the preparation method of the foam stabilizer includes the following steps: under a nitrogen atmosphere, low hydrogen-containing silicone oil, octamethylcyclotetrasiloxane, hexamethyldisiloxane and isopropanol are added to a reaction flask and dispersed, a catalyst is added, the temperature is controlled at 90-100℃, allyl polyether is added, the reaction is kept at the temperature for 3-6 hours, and the solvent and low-boiling substances are removed by vacuum distillation to obtain the foam stabilizer.

[0041] Low-hydrogen silicone oil viscosity 20-120 mm 2 / s, active hydrogen 0.1-0.3%;

[0042] Allyl polyethers have a molecular weight of 500-1500 and an unsaturation degree of 0.65-2.1 mmol / g;

[0043] The catalyst is a platinum-based catalyst; the addition ratio of low-hydrogen silicone oil, octamethylcyclotetrasiloxane, hexamethyldisiloxane, isopropanol, catalyst, and allyl polyether is 100g: 20-50g: 5-15g: 100-200mL: 0.02-0.06g: 30-80g.

[0044] A foam silicone thermal insulation material, made by any of the above preparation methods.

[0045] Beneficial effects:

[0046] (1) Low thermal conductivity and thermal insulation performance

[0047] This application generates H2 foam through the hydrosilylation reaction of hydrogen-containing silicone oil and water, forming a uniform and dense closed-cell structure. The micron-sized pores significantly reduce the overall density of the material, and the low thermal conductivity of air blocks heat conduction.

[0048] This application incorporates nano-deposited hydrophobically modified SiO2 aerogel powder. The deposition of nano-silica sol on the aerogel surface forms a mesoporous structure, effectively suppressing convective heat transfer from gas molecules. Simultaneously, the low solid-phase thermal conductivity of the deposited layer further enhances the insulation effect. The native mesopores within the nano-deposited hydrophobically modified SiO2 aerogel powder provide nanoscale insulation units. This application utilizes micropores, mesopores, and nanopores to construct a synergistic insulation network, achieving both low thermal conductivity and excellent insulation performance in the material.

[0049] (2) Interfacial chemical bonding and low powder shedding performance

[0050] This application incorporates nano-deposited hydrophobically modified SiO2 aerogel powder, amino-terminated dimethyl silicone oil, alkoxy-functionalized hydrogen-containing silicone oil, and modified vinyl silicone oil into the material. The nano-deposited hydrophobically modified SiO2 aerogel powder is prepared by depositing silica sol onto hydrophobically modified silica aerogel. The nano-SiO2 particles partially enter the pores on the aerogel surface, forming mechanical interlocks. Simultaneously, the deposited layer surface is rich in silanol groups, providing numerous chemical bonding sites, achieving a synergistic enhancement of physical anchoring and chemical bonding. The alkoxy-functionalized hydrogen-containing silicone oil is prepared by grafting VTES onto hydrogen-containing silicone oil. The alkoxy groups hydrolyze to generate silanol groups, which condense with hydroxyl groups on the aerogel surface to form ≡Si-O-Si≡ covalent bonds. Because the hydrogen-containing silicone oil itself participates in the cross-linking network, the aerogel is directly chemically anchored within the three-dimensional silica framework. The terminal amino groups of amino-terminated dimethyl silicone oil form strong hydrogen bonds with the hydroxyl groups on the aerogel surface and can react with epoxy groups during vulcanization to form chemical bonds. This anchors one end of the dimethyl silicone oil molecular chain to the aerogel surface while the other end extends into the matrix, forming a flexible molecular brush layer. This molecular brush not only provides steric hindrance to prevent aggregation but also buffers stress and prevents interfacial debonding under load. Modified vinyl silicone oil is prepared by bridging epoxy and amino groups with the side chains of vinyl silicone oil. The epoxy and amino groups form hydrogen bonds and covalent bonds with the hydroxyl groups on the aerogel surface and the nano-SiO2 deposition layer of the nano-deposited hydrophobic modified SiO2 aerogel powder, further strengthening the interfacial bonding strength.

[0051] This application utilizes the synergistic effect of nano-deposition hydrophobically modified SiO2 aerogel powder, amino-terminated modified dimethyl silicone oil, alkoxy-functionalized hydrogen-containing silicone oil, and modified vinyl silicone oil to upgrade the interfacial bonding between the aerogel and the silicone matrix from physical blending to a chemical bonding network, fundamentally eliminating the risk of powder shedding.

[0052] (3) Excellent compression resilience and cushioning and vibration damping performance

[0053] The foaming agent added in this application reduces the interfacial tension between oil and water, enabling the H2 bubble nuclei to be evenly distributed and grow stably, forming a closed-cell structure with uniform bubble size and consistent wall thickness. The uniformly distributed bubbles share the stress during compression, avoiding stress concentration; after unloading, the elastic recovery force of the bubble walls is released simultaneously, allowing the material to quickly return to its original shape. This application also adds amino-terminated modified dimethyl silicone oil and nano-deposited hydrophobically modified SiO2 aerogel powder, serving as a flexible transition layer between the rigid aerogel framework and the silicone matrix. During compression, these layers absorb some energy through molecular chain conformational changes, reducing the direct transfer of stress to the aerogel particles and protecting the aerogel structure from damage. This application adds alkoxy-functionalized hydrogen-containing silicone oil stepwise, ensuring uniform dispersion of the crosslinking agent in component A while retaining sufficient fresh Si-H bonds in component C, allowing the crosslinking reaction during the foaming stage to proceed fully. Secondary vulcanization completely completes the residual crosslinking reaction, saturates the crosslinking density, maximizes the mechanical strength of the bubble walls, and endows the material with excellent creep resistance.

[0054] (4) High flame retardant performance

[0055] This application uses silicone as the matrix, with the silicone rubber main chain having a Si-O-Si inorganic structure. During combustion, it decomposes to generate a SiO2 protective layer, isolating oxygen and heat transfer, thus possessing inherent flame-retardant properties. The nano-deposited hydrophobically modified SiO2 aerogel powder maintains structural stability at high temperatures, and its nanoporous structure effectively blocks heat feedback in the early stages of combustion, delaying material thermal decomposition. The modified vinyl silicone oil is prepared by introducing epoxy and amino groups into the side chains of vinyl silicone oil. These epoxy and amino groups promote char formation at high temperatures, forming a dense char layer that further blocks the diffusion of combustible gases. Finally, this application also performs secondary vulcanization on the material to remove residual low-molecular-weight substances, further improving its flame-retardant performance.

[0056] (5) Precise control of ultra-thin thickness and process stability

[0057] This application adds alkoxy-functionalized hydrogen-containing silicone oil in stages. Part of the alkoxy-functionalized hydrogen-containing silicone oil is added to component A to ensure uniform high-temperature dispersion of the crosslinking agent. The remaining alkoxy-functionalized hydrogen-containing silicone oil is added during the foaming stage to provide fresh, highly active Si-H bonds. The first part ensures macroscopic dispersion uniformity, and the second part ensures sufficient foaming kinetics. This application also adds a foam leveling agent, which ensures uniform distribution of bubble nuclei, preventing excessive growth or merging of localized cells, and ensuring good cell consistency and uniform thickness in the width direction of the thin sheet. Finally, by controlling the matching relationship between the calendering roll gap and the foaming ratio, this application can precisely control the final thickness within the target range. Three-stage gradient vulcanization matches the foaming and crosslinking rates, preventing excessive bubble growth leading to excessive thickness or insufficient foaming leading to insufficient thickness.

[0058] (6) Environmental protection and safety of water-based foaming systems

[0059] This solution uses deionized water as the sole foaming agent, generating H2 foam through the hydrosilylation reaction of hydrogen-containing silicone oil and water. It completely eliminates traditional chemical foaming agents such as azodicarbonamide (AC) and OBSH, thus preventing the generation of harmful decomposition products such as NH3, CO, and formamide, and significantly reducing VOC emissions.

[0060] This invention aims to overcome the shortcomings of existing technologies and provide an ultra-thin aerogel-modified foamed silicone rubber foam suitable for 3C electronic products. The goal is to achieve uniform and stable dispersion of aerogel powder within a foamed silicone rubber matrix on ultra-thin sheets with a thickness of only about 1.0 mm, avoiding cell deterioration and mechanical property degradation caused by agglomeration. Simultaneously, it enhances the interfacial bonding between the aerogel and the silicone rubber matrix to eliminate the risk of powder shedding. This results in an aerogel-modified foamed silicone rubber foam that possesses low thermal conductivity, good compression resilience, no powder shedding, flame retardancy, and a controllable thickness within the range of 1.0 mm ± 0.1 mm, meeting the increasingly stringent thermal management and reliability requirements of 3C electronic products. Detailed Implementation

[0061] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0062] Example 1: The preparation method of modified vinyl silicone oil includes the following steps:

[0063] Under a nitrogen atmosphere, 100g of vinyl silicone oil (viscosity 8000mPa·s, vinyl content 0.16wt%) and 100mL of isopropanol were added to a reaction flask for dispersion. 0.01g of Castells platinum catalyst was added, and the temperature was controlled at 90℃. 2g of allyl glycidyl ether was added, and the reaction was maintained at this temperature for 2h. 1g of allylamine was added, and the reaction was maintained at this temperature for 2h. Isopropanol and unreacted monomers were removed by vacuum distillation to obtain modified vinyl silicone oil.

[0064] The preparation method of alkoxy-functionalized hydrogen-containing silicone oil includes the following steps: Under a nitrogen atmosphere, 100g of hydrogen-containing silicone oil (viscosity 100mm) is added... 2 / s, active hydrogen 0.7%), and 100mL of toluene were added to the reaction flask for dispersion. 0.02g of Castel platinum catalyst was added, and the temperature was controlled at 90℃. 5g of vinyltriethoxysilane was added, and the reaction was kept at this temperature for 4h. Toluene and unreacted substances were removed by vacuum distillation to obtain alkoxy-functionalized hydrogen-containing silicone oil.

[0065] The preparation method of amino-terminated modified dimethyl silicone oil includes the following steps: 100g of hydroxyl-terminated dimethyl silicone oil (viscosity 30mm) is mixed with... 2 10g of dimethyl silicone oil (containing 9wt% hydroxyl content) was added to a reaction flask and dispersed. The temperature was controlled at 60℃. 5g of aminoethylaminopropyldimethoxysilane was added and the reaction was maintained at this temperature for 4h. Methanol was removed by vacuum distillation to obtain amino-terminated modified dimethyl silicone oil.

[0066] The preparation method of the foaming agent includes the following steps: Under a nitrogen atmosphere, 100g of low-hydrogen-content silicone oil (viscosity 80mm) is added... 2 20g of octamethylcyclotetrasiloxane, 5g of hexamethyldisiloxane, and 100mL of isopropanol were added to a reaction flask and dispersed. 0.02g of Castel platinum catalyst was added, and the temperature was controlled at 90℃. 30g of allyl polyether (molecular weight 1000, unsaturation 1.3mmol / g) was added, and the reaction was kept at this temperature for 3h. The solvent and low-boiling substances were removed by vacuum distillation to obtain a foaming agent.

[0067] The preparation method of nano-deposited hydrophobically modified SiO2 aerogel powder includes the following steps:

[0068] A1: In a nitrogen atmosphere, 100g of silica aerogel powder (pore size 20nm, specific surface area 500m²) was placed... 2 / g) is added to a closed gas-phase modification reactor, heated to 120℃, 5g of trimethylchlorosilane and 5g of hexamethyldisilazane are mixed and vaporized, and nitrogen is introduced into the gas-phase modification reactor with nitrogen as carrier (carrier gas flow rate 1L / min). The reaction is kept at the temperature for 2h, and the nitrogen vapor containing trimethylchlorosilane and hexamethyldisilazane is stopped. Nitrogen is used to purge unreacted trimethylchlorosilane, hexamethyldisilazane and by-products to obtain trimethylsiloxy hydrophobic graft modified aerogel powder;

[0069] A2: Add 180 mL of anhydrous ethanol and 45 mL of deionized water to the reaction flask and mix. Add 0.1 mol / L dilute hydrochloric acid to adjust the pH of the system to 5. Control the temperature at 40℃. Add 100 g of tetraethyl orthosilicate dropwise. Keep the reaction at the temperature for 3 h under stirring. Raise the temperature to 50℃ and keep it at the temperature for 1 h. Cool down to room temperature and add anhydrous ethanol to dilute. Obtain a nano SiO2 sol solution with a solid content of 12 wt%.

[0070] A3: Trimethylsiloxy hydrophobic grafted modified aerogel powder was added to a reaction vessel, and nano-SiO2 sol was added. The mixture was stirred at 300 r / min at room temperature for 25 min to deposit the aerogel. The temperature was controlled at 55℃ and the reaction was carried out for 0.5 h. The aerogel was then passed through a 120-mesh sieve and dried to obtain nano-deposited hydrophobic modified SiO2 aerogel powder.

[0071] A method for preparing a foamed silicone thermal insulation material includes the following steps:

[0072] 100 parts by weight of the modified vinyl silicone oil prepared in Example 1 and 10 parts by weight of hydroxyl silicone oil (viscosity 30 mm) were mixed. 2 / s, hydroxyl content 8.5%), 2 parts by weight of alkoxy-functionalized hydrogen-containing silicone oil prepared in Example 1, and 10 parts by weight of fumed silica were added to a kneader and kneaded under vacuum at 125°C for 3 hours to obtain component A;

[0073] 20 parts by weight of the nano-deposited hydrophobic modified SiO2 aerogel powder prepared in Example 1 and 8 parts by weight of the amino-terminated functionalized dimethyl silicone oil prepared in Example 1 were blended to obtain an aerogel pre-dispersion slurry.

[0074] Component A, aerogel pre-dispersion slurry, 4 parts by weight of dimethyl silicone oil (viscosity 200 mPa·s), 1.8 parts by weight of the foaming agent prepared in Example 1, 3 parts by weight of the alkoxy-functionalized hydrogen-containing silicone oil prepared in Example 1, and 0.1 parts by weight of 2-methyl-3-butyn-2-ol were stirred at 500 rpm for 30 min. Then, 1.5 parts by weight of deionized water and 0.3 parts by weight of Castel platinum catalyst were added, and the mixture was stirred at 1000 rpm for 5 min to obtain foamed adhesive.

[0075] The foamed rubber was calendered, vulcanized at 110℃ for 2 min, 140℃ for 3 min, 170℃ for 5 min, and 215℃ for 3 h to obtain a 1 mm thick foamed silicone insulation material.

[0076] Example 2: The preparation method of modified vinyl silicone oil includes the following steps:

[0077] Under a nitrogen atmosphere, 100g of vinyl silicone oil (viscosity 8000mPa·s, vinyl content 0.16wt%) and 150mL of isopropanol were added to a reaction flask for dispersion. 0.03g of Castells platinum catalyst was added, and the temperature was controlled at 95℃. 5g of allyl glycidyl ether was added, and the reaction was maintained at this temperature for 3h. 3g of allylamine was added, and the reaction was maintained at this temperature for 3h. Isopropanol and unreacted monomers were removed by vacuum distillation to obtain modified vinyl silicone oil.

[0078] The preparation method of alkoxy-functionalized hydrogen-containing silicone oil includes the following steps: Under a nitrogen atmosphere, 100g of hydrogen-containing silicone oil (viscosity 100mm) is added... 2 / s, active hydrogen 0.7%), and 150mL toluene were added to the reaction flask for dispersion. 0.05g of Castel platinum catalyst was added, and the temperature was controlled at 100℃. 10g of vinyltriethoxysilane was added, and the reaction was kept at this temperature for 6h. Toluene and unreacted substances were removed by vacuum distillation to obtain alkoxy-functionalized hydrogen-containing silicone oil.

[0079] The preparation method of amino-terminated modified dimethyl silicone oil includes the following steps: 100g of hydroxyl-terminated dimethyl silicone oil (viscosity 30mm) is mixed with... 2 20g of dimethyl silicone oil (containing 9wt% hydroxyl content) was added to a reaction flask and dispersed. The temperature was controlled at 70℃. 12g of aminoethylaminopropyldimethoxysilane was added and the reaction was maintained at this temperature for 5h. Methanol was removed by vacuum distillation to obtain amino-terminated modified dimethyl silicone oil.

[0080] The preparation method of the foaming agent includes the following steps: Under a nitrogen atmosphere, 100g of low-hydrogen-content silicone oil (viscosity 80mm) is added... 2=35g of octamethylcyclotetrasiloxane, 10g of hexamethyldisiloxane, and 150mL of isopropanol were added to the reaction flask and dispersed. 0.04g of Castel platinum catalyst was added and the temperature was controlled at 95℃. 55g of allyl polyether (molecular weight 1000, unsaturation 1.3mmol / g) was added and the reaction was kept at this temperature for 4.5h. The solvent and low-boiling substances were removed by vacuum distillation to obtain the foaming agent.

[0081] The preparation method of nano-deposited hydrophobically modified SiO2 aerogel powder includes the following steps:

[0082] A1: In a nitrogen atmosphere, 100g of silica aerogel powder (pore size 20nm, specific surface area 500m²) was placed... 2 / g) is added to a closed gas-phase modification reactor, heated to 125℃, 10g of trimethylchlorosilane and 10g of hexamethyldisilazane are mixed and vaporized, and nitrogen is introduced into the gas-phase modification reactor with nitrogen as carrier (carrier gas flow rate 1L / min). The reaction is kept at the temperature for 3h, and the nitrogen vapor containing trimethylchlorosilane and hexamethyldisilazane is stopped. Nitrogen is used to purge unreacted trimethylchlorosilane, hexamethyldisilazane and by-products to obtain trimethylsiloxy hydrophobic graft modified aerogel powder;

[0083] A2: Add 200 mL of anhydrous ethanol and 50 mL of deionized water to the reaction flask and mix. Add 0.1 mol / L dilute hydrochloric acid to adjust the pH of the system to 5.5. Control the temperature at 40℃. Add 100 g of tetraethyl orthosilicate dropwise. Keep the reaction at the temperature for 4 h under stirring. Raise the temperature to 55℃ and keep it at the temperature for 1.5 h. Cool down to room temperature and dilute with anhydrous ethanol to obtain a nano SiO2 sol solution with a solid content of 12 wt%.

[0084] A3: Trimethylsiloxy hydrophobic grafted modified aerogel powder was added to a reaction vessel, and nano-SiO2 sol was added. The mixture was stirred at 300 r / min at room temperature for 30 min to deposit the aerogel. The temperature was controlled at 60℃ and the reaction was carried out for 0.5 h. The aerogel was then passed through a 120-mesh sieve and dried to obtain nano-deposited hydrophobic modified SiO2 aerogel powder.

[0085] A method for preparing a foam silicone thermal insulation material, compared with Example 1, only the modified vinyl silicone oil, alkoxy-functionalized hydrogen-containing silicone oil, nano-deposited hydrophobic modified SiO2 aerogel powder, amino-terminated functionalized dimethyl silicone oil, and foam stabilizer prepared in Example 1 are replaced in equal amounts with the modified vinyl silicone oil, alkoxy-functionalized hydrogen-containing silicone oil, nano-deposited hydrophobic modified SiO2 aerogel powder, amino-terminated functionalized dimethyl silicone oil, and foam stabilizer prepared in Example 2. The remaining components and preparation methods are completely consistent with Example 1.

[0086] Example 3: The preparation method of modified vinyl silicone oil includes the following steps:

[0087] Under a nitrogen atmosphere, 100g of vinyl silicone oil (viscosity 8000mPa·s, vinyl content 0.16wt%) and 200mL of isopropanol were added to a reaction flask for dispersion. 0.05g of Castells platinum catalyst was added, and the temperature was controlled at 100℃. 8g of allyl glycidyl ether was added, and the reaction was maintained at this temperature for 4h. 5g of allyl amine was added, and the reaction was maintained at this temperature for 4h. Isopropanol and unreacted monomers were removed by vacuum distillation to obtain modified vinyl silicone oil.

[0088] The preparation method of alkoxy-functionalized hydrogen-containing silicone oil includes the following steps: Under a nitrogen atmosphere, 100g of hydrogen-containing silicone oil (viscosity 100mm) is added... 2 / s, active hydrogen 0.7%), and 200mL toluene were added to the reaction flask for dispersion. 0.08g of Castel platinum catalyst was added, and the temperature was controlled at 110℃. 15g of vinyltriethoxysilane was added, and the reaction was kept at this temperature for 8h. Toluene and unreacted substances were removed by vacuum distillation to obtain alkoxy-functionalized hydrogen-containing silicone oil.

[0089] The preparation method of amino-terminated modified dimethyl silicone oil includes the following steps: 100g of hydroxyl-terminated dimethyl silicone oil (viscosity 30mm) is mixed with... 2 30g of dimethyl silicone oil (containing 9wt% hydroxyl content) was added to a reaction flask and dispersed. The temperature was controlled at 80℃. 20g of aminoethylaminopropyldimethoxysilane was added and the reaction was maintained at this temperature for 6h. Methanol was removed by vacuum distillation to obtain amino-terminated modified dimethyl silicone oil.

[0090] The preparation method of the foaming agent includes the following steps: Under a nitrogen atmosphere, 100g of low-hydrogen-content silicone oil (viscosity 80mm) is added... 2 50g of octamethylcyclotetrasiloxane, 15g of hexamethyldisiloxane, and 200mL of isopropanol were added to a reaction flask and dispersed. 0.06g of Castel platinum catalyst was added, and the temperature was controlled at 100℃. 80g of allyl polyether (molecular weight 1000, unsaturation 1.3mmol / g) was added, and the reaction was kept at this temperature for 6h. The solvent and low-boiling substances were removed by vacuum distillation to obtain a foaming agent.

[0091] The preparation method of nano-deposited hydrophobically modified SiO2 aerogel powder includes the following steps:

[0092] A1: In a nitrogen atmosphere, 100g of silica aerogel powder (pore size 20nm, specific surface area 500m²) was placed... 2 / g) is added to a closed gas-phase modification reactor, heated to 130℃, 15g of trimethylchlorosilane and 15g of hexamethyldisilazane are mixed and vaporized, and nitrogen is introduced into the gas-phase modification reactor with nitrogen as carrier (carrier gas flow rate 1L / min). The reaction is kept at the temperature for 4h, and the nitrogen vapor containing trimethylchlorosilane and hexamethyldisilazane is stopped. Nitrogen is used to purge unreacted trimethylchlorosilane, hexamethyldisilazane and by-products to obtain trimethylsiloxy hydrophobic graft modified aerogel powder;

[0093] A2: Add 220 mL of anhydrous ethanol and 55 mL of deionized water to the reaction flask and mix. Add 0.1 mol / L dilute hydrochloric acid to adjust the pH of the system to 5.5. Control the temperature at 45℃. Add 100 g of tetraethyl orthosilicate dropwise. Keep the reaction at the temperature for 5 h under stirring. Raise the temperature to 55℃ and keep it constant for 1.5 h. Cool down to room temperature and dilute with anhydrous ethanol to obtain a nano SiO2 sol solution with a solid content of 12 wt%.

[0094] A3: Trimethylsiloxy hydrophobic grafted modified aerogel powder was added to a reaction vessel, and nano-SiO2 sol was added. The mixture was stirred at 300 r / min at room temperature for 35 min to deposit the aerogel. The temperature was controlled at 65℃ and the reaction was carried out for 1 h. The aerogel was then passed through a 120-mesh sieve and dried to obtain nano-deposited hydrophobic modified SiO2 aerogel powder.

[0095] A method for preparing a foam silicone thermal insulation material, compared with Example 1, only the modified vinyl silicone oil, alkoxy-functionalized hydrogen-containing silicone oil, nano-deposited hydrophobic modified SiO2 aerogel powder, amino-terminated functionalized dimethyl silicone oil, and foam stabilizer prepared in Example 1 are replaced in equal amounts with the modified vinyl silicone oil, alkoxy-functionalized hydrogen-containing silicone oil, nano-deposited hydrophobic modified SiO2 aerogel powder, amino-terminated functionalized dimethyl silicone oil, and foam stabilizer prepared in Example 3. The remaining components and preparation methods are completely consistent with Example 1.

[0096] Comparative Example 1: A method for preparing a foamed silicone thermal insulation material. Compared with Example 1, only the modified vinyl silicone oil prepared in Example 1 is replaced in equal amounts with the vinyl silicone oil used in Example 1. The remaining components and preparation methods are completely consistent with Example 1.

[0097] Comparative Example 2: The preparation method of hydrophobically modified SiO2 aerogel powder includes the following steps: In a nitrogen atmosphere, 100g of silica aerogel powder (pore size 20nm, specific surface area 500m²) is added... 2 / g) is added to a closed gas-phase modification vessel, heated to 125℃, 10g of trimethylchlorosilane and 10g of hexamethyldisilazane are mixed and vaporized, and nitrogen is introduced into the gas-phase modification vessel with nitrogen as the carrier (carrier gas flow rate 1L / min). The reaction is kept at the temperature for 3h, and the nitrogen vapor containing trimethylchlorosilane and hexamethyldisilazane is stopped. Nitrogen is used to purge unreacted trimethylchlorosilane, hexamethyldisilazane and by-products to obtain hydrophobically modified SiO2 aerogel powder.

[0098] A method for preparing a foamed silicone thermal insulation material, compared with Example 1, is that the nano-deposited hydrophobic modified SiO2 aerogel powder prepared in Example 1 is replaced in equal amounts with the hydrophobic modified SiO2 aerogel powder prepared in Comparative Example 2, and the remaining components and preparation methods are completely the same as in Example 1.

[0099] Comparative Example 3: A method for preparing a foamed silicone thermal insulation material. Compared with Example 1, only the alkoxy-functionalized hydrogen-containing silicone oil prepared in Example 1 is replaced in equal amounts with the hydrogen-containing silicone oil prepared in Example 1. The remaining components and preparation methods are completely consistent with Example 1.

[0100] Comparative Example 4: A method for preparing a foam silicone thermal insulation material. Compared with Example 1, the only difference is that the amino-terminated dimethyl silicone oil prepared in Example 1 is replaced in equal amounts with the hydroxyl-terminated dimethyl silicone oil prepared in Example 1. The remaining components and preparation methods are completely consistent with Example 1.

[0101] Comparative Example 5: A method for preparing a foamed silicone thermal insulation material. Compared with Example 1, only the amino-terminated modified dimethyl silicone oil prepared in Example 1 was removed. The remaining components and preparation method are completely consistent with Example 1.

[0102] Comparative Example 6: A method for preparing a foamed silicone thermal insulation material. Compared with Example 1, only the foaming agent prepared in Example 1 is removed, while the remaining components and preparation method are completely the same as in Example 1.

[0103] Comparative Example 7: A method for preparing a foam silicone thermal insulation material, comprising the following steps:

[0104] 100 parts by weight of the modified vinyl silicone oil prepared in Example 1 and 10 parts by weight of hydroxyl silicone oil (viscosity 30 mm) were mixed. 2 5 parts by weight of alkoxy-functionalized hydrogen-containing silicone oil prepared in Example 1 (8.5% hydroxyl content), and 10 parts by weight of fumed silica were added to a kneader and kneaded under vacuum at 125°C for 3 hours to obtain component A.

[0105] 20 parts by weight of the nano-deposited hydrophobic modified SiO2 aerogel powder prepared in Example 1 and 8 parts by weight of the amino-terminated functionalized dimethyl silicone oil prepared in Example 1 were blended to obtain an aerogel pre-dispersion slurry.

[0106] Component A, aerogel pre-dispersion slurry, 4 parts by weight of dimethyl silicone oil (viscosity 200 mPa·s), 1.8 parts by weight of the foaming agent prepared in Example 1, and 0.1 parts by weight of 2-methyl-3-butyn-2-ol were stirred at 500 rpm for 30 min. Then, 1.5 parts by weight of deionized water and 0.3 parts by weight of Castel platinum catalyst were added, and the mixture was stirred at 1000 rpm for 5 min to obtain foamed adhesive.

[0107] The foamed rubber was calendered, vulcanized at 110℃ for 2 min, 140℃ for 3 min, 170℃ for 5 min, and 215℃ for 3 h to obtain a 1 mm thick foamed silicone insulation material.

[0108] Comparative Example 8: A method for preparing a foam silicone thermal insulation material, comprising the following steps:

[0109] 100 parts by weight of the modified vinyl silicone oil prepared in Example 1 and 10 parts by weight of hydroxyl silicone oil (viscosity 30 mm) were mixed. 2 / s, hydroxyl content 8.5%), 2 parts by weight of alkoxy-functionalized hydrogen-containing silicone oil prepared in Example 1, and 10 parts by weight of fumed silica were added to a kneader and kneaded under vacuum at 125°C for 3 hours to obtain component A;

[0110] 20 parts by weight of the nano-deposited hydrophobic modified SiO2 aerogel powder prepared in Example 1 and 8 parts by weight of the amino-terminated functionalized dimethyl silicone oil prepared in Example 1 were blended to obtain an aerogel pre-dispersion slurry.

[0111] Component A, aerogel pre-dispersion slurry, 4 parts by weight of dimethyl silicone oil (viscosity 200 mPa·s), 1.8 parts by weight of the foaming agent prepared in Example 1, 3 parts by weight of the alkoxy-functionalized hydrogen-containing silicone oil prepared in Example 1, and 0.1 parts by weight of 2-methyl-3-butyn-2-ol were stirred at 500 rpm for 30 min. Then, 1.5 parts by weight of deionized water and 0.3 parts by weight of Castel platinum catalyst were added, and the mixture was stirred at 1000 rpm for 5 min to obtain foamed adhesive.

[0112] The foamed rubber was calendered and then vulcanized at 110°C for 2 minutes, 140°C for 3 minutes, and 170°C for 5 minutes to obtain a 1 mm thick foamed silicone insulation material.

[0113] Performance testing

[0114] Thermal conductivity: The test results were obtained according to GB / T 10295-2008 "Determination of steady-state thermal resistance and related properties of thermal insulation materials by heat flow meter method". The test results are shown in Table 1.

[0115] Apparent density: The apparent density was tested according to GB / T 6343-2009 "Determination of apparent density of foamed plastics and rubber". The test results are shown in Table 1.

[0116] Flame retardancy rating: Tested according to GB / T 2408-2008 "Determination of flammability of plastics - Horizontal and Vertical Methods", the test results are shown in Table 1;

[0117] Dust shedding resistance: The test was conducted according to GB / T 2423.37-2006 "Environmental testing for electrical and electronic products - Part 2: Test methods - Test L: Dust test", and the amount of shed particulate matter was calculated. The test results are shown in Table 1.

[0118] Table 1: Statistical table of physicochemical properties of Examples 1-3 and Comparative Examples 1-8

[0119] thermal conductivity Surface density Flame retardant rating <![CDATA[Shed particles / (mg / 100cm 2 )]]>< Example 1 0.032 0.38 V-0 0.3 Example 2 0.030 0.36 V-0 0.2 Example 3 0.034 0.40 V-0 0.5 Comparative Example 1 0.045 0.43 V-1 2.4 Comparative Example 2 0.042 0.42 V-0 3.8 Comparative Example 3 0.040 0.41 V-0 4.2 Comparative Example 4 0.048 0.45 V-0 8.5 Comparative Example 5 0.044 0.42 V-0 1.2 Comparative Example 6 0.050 0.53 V-0 15.0 Comparative Example 7 0.039 0.35 V-0 0.8 Comparative Example 8 0.055 0.45 V-1 12.0

[0120] Compression set: According to GB / T 7759.1-2015 "Determination of compression set of vulcanized rubber or thermoplastic rubber", the rubber was compressed by 50% and heated to 70℃ for 22 hours. After 30 minutes of recovery, the thickness change was measured and the compression set rate was calculated. The test results are shown in Table 2.

[0121] Resilience rate: According to GB / T 6670-2008 "Determination of resilience of flexible foam polymer materials by falling ball method", the test results are shown in Table 2;

[0122] Buffering energy absorption and stiffness: According to GB / T 18942.1-2003 "Determination of compressive stress-strain characteristics of porous polymer materials", the compression rate was 50 mm / min, and the compressive stress at 25% and 50% was recorded. The test results are shown in Table 2.

[0123] Table 2: Elasticity Data Statistics of Examples 1-3 and Comparative Examples 1-8

[0124] Compression permanent deformation rate / % Rebound rate / % 25% compressive stress / kPa 50% compressive stress / kPa Example 1 4.2 52 28 65 Example 2 3.8 55 25 58 Example 3 4.8 48 32 72 Comparative Example 1 8.5 38 35 80 Comparative Example 2 7.2 42 32 75 Comparative Example 3 9.0 35 38 85 Comparative Example 4 12.5 28 42 95 Comparative Example 5 6.8 45 30 70 Comparative Example 6 18.0 20 55 120 Comparative Example 7 8.5 40 25 55 Comparative Example 8 15.0 25 48 105

[0125] As shown in Tables 1-2, compared to Example 1, Comparative Example 1, which only replaced the modified vinyl silicone oil added in Example 1 with vinyl silicone oil, exhibited the following effects: thermal conductivity increased from 0.032 to 0.045 W / (m·K), resilience decreased from 52% to 38%, flame retardancy decreased from V-0 to V-1, and dust shedding increased from 0.3 to 2.5 mg / 100 cm³. 2The modified vinyl silicone oil used in Example 1, with the introduction of epoxy and amino groups into its side chains, significantly increased its polarity and reduced the interfacial tension between it and the polar aerogel powder. This improved dispersion uniformity, resulting in greater thermal resistance between uniformly dispersed aerogel particles and a significantly lower thermal conductivity. Simultaneously, it reduced stress concentration points, leading to improved resilience and flame retardancy. The enhanced interfacial bonding also made the aerogel particles less prone to detachment from the matrix under stress, resulting in a substantial reduction in powder shedding.

[0126] Compared to Example 1, the silica aerogel of Comparative Example 2 underwent only gas-phase hydrophobic modification with trimethylchlorosilane / hexamethyldisilazane. The powder shedding of Comparative Example 2 increased from 0.3 mg / 100 cm³ to 3.8 mg / 100 cm³. 2 The thermal conductivity increased from 0.032 to 0.042 W / (m·K), and the compression set increased from 4.2% to 7.2%. The nano-deposited hydrophobic modified SiO2 aerogel powder used in Example 1 utilizes the deposition of nano-SiO2 particles on the surface of the aerogel and in the mesoporous channels of the aerogel, effectively reducing the amount of powder shedding; and the nano-SiO2 deposition layer itself has a mesoporous structure, which reduces the thermal conductivity.

[0127] Compared to Example 1, Comparative Example 3 used only unmodified hydrogen-containing silicone oil, and the powder shedding rate of Comparative Example 3 increased from 0.3 mg / 100 cm³ to 4.2 mg / 100 cm³. 2 The compression set increased from 4.2% to 9.0%, and the thermal conductivity increased from 0.032 to 0.040 W / (m·K). The alkoxy-functionalized hydrogen-containing silicone oil used in Example 1 was prepared by introducing triethoxysilane groups into hydrogen-containing silicone oil. The alkoxy groups hydrolyze under humid and hot conditions during the kneading of component A and subsequent vulcanization to generate silanol groups. These silanol groups undergo a condensation reaction with the silanol groups on the surface of the nano-deposited aerogel, directly anchoring the aerogel particles to the three-dimensional silicone network via covalent bonds, effectively reducing compression set and powder loss.

[0128] Compared to Example 1, Comparative Examples 4 and 5 differed in that Comparative Example 4 replaced the hydroxyl-terminated dimethyl silicone oil used in Example 1 with the amino-terminated dimethyl silicone oil; Comparative Example 5 removed the amino-terminated dimethyl silicone oil used in Example 1; and Comparative Example 4 exhibited a powder shedding rate as high as 8.5 mg / 100 cm³. 2 The rebound rate was only 28%, and the compression set was 12.5%; the comparative example 5 had a powder loss of 1.2 mg / 100 cm³. 2The rebound rate was 45%, and the thermal conductivity was 0.044 W / (m·K). Its performance was significantly inferior to Example 1. Although the terminal hydroxyl dimethyl silicone oil added to Comparative Example 4 contained polar hydroxyl groups, it was insufficient to resist shear stress during processing and compression deformation during use. Under the high shear conditions of mechanical stirring and calendering, the physically adsorbed silicone oil layer was easily destroyed, leading to aerogel re-agglomeration. Therefore, Comparative Example 4 showed the most severe performance degradation. Comparative Example 5 did not contain terminal amino silicone oil; the aerogel powder was directly added to the silicone system, and the nanoparticles rapidly agglomerated due to their high specific surface energy. These agglomerates became defect points for cell nucleation during foaming, resulting in uneven cell structure, increased macropore defects, and increased thermal conductivity. Simultaneously, the lack of effective interfacial bonding between the agglomerates and the matrix created stress concentration points, leading to decreased compression resilience.

[0129] Compared to Example 1, Comparative Example 6 removed the foaming agent used in Example 1; the thermal conductivity of Comparative Example 6 increased to 0.050 W / (m·K), and the apparent density increased to 0.52 g / cm³. 3 The rebound rate dropped to 20%, and powder shedding soared to 15.0mg / 100cm. 2 The foam stabilizer prepared in this application is an amphiphilic comb copolymer, in which the polyether segments are hydrophilic and the siloxane segments are lipophilic, playing multiple functions in the foaming system. Without the foam stabilizer, the aerogel agglomerates severely and cannot perform its heat insulation function.

[0130] Compared to Example 1, Comparative Example 7 added all the hydrogen-containing silicone oil to component A at once, resulting in a lower final density, a thermal conductivity of 0.038 W / (m·K), and a resilience of 40%. Although the Si-H bonds in the hydrogen-containing silicone oil are relatively stable at room temperature, under high temperature and vacuum kneading conditions of 125°C for 3 hours, some Si-H bonds inevitably underwent thermal oxidation decomposition and dehydrogenation side reactions, leading to a decrease in the active hydrogen content. When all the hydrogen-containing silicone oil underwent high-temperature kneading, and water and catalyst were added in step five for foaming, the number of remaining reactive Si-H bonds was insufficient, resulting in reduced foaming kinetics, poor resilience, and increased compression set.

[0131] Compared to Example 1, Comparative Example 8, by omitting the secondary vulcanization step, exhibits a high thermal conductivity of 0.055 W / (m·K), a compression set of 15.0%, and a dust loss of 12.0 mg / 100 cm³. 2 The flame retardancy decreased to V-1. While conventional foaming vulcanization (170℃×10min) completed the main crosslinking, the hydrosilylation and condensation reactions were kinetically limited at lower temperatures, resulting in some reactions not proceeding completely. Vulcanization at 215℃ for 3 hours provided sufficient thermal activation energy, allowing the remaining Si-H bonds and vinyl groups, as well as the remaining silanol groups, to react further, reaching a saturation point for crosslinking density. In contrast, Comparative Example 8, without secondary vulcanization, showed insufficient crosslinking, increased compression set, higher thermal conductivity, and increased powder shedding.

[0132] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.

Claims

1. A method for preparing a foamed silicone thermal insulation material, characterized in that, Includes the following steps: Modified vinyl silicone oil, hydroxyl silicone oil, partially alkoxy-functionalized hydrogen-containing silicone oil, and fumed silica were blended to obtain component A. Nanoparticle-deposited hydrophobically modified SiO2 aerogel powder and amino-terminated functionalized dimethyl silicone oil were blended to obtain aerogel pre-dispersion slurry; Component A, aerogel pre-dispersion slurry, dimethyl silicone oil, foam stabilizer, remaining alkoxy-functionalized hydrogen-containing silicone oil, and inhibitor are blended together, and deionized water and catalyst are added and blended together to obtain foamed adhesive. The foamed rubber is calendered and vulcanized to obtain foamed silicone insulation material; The nano-deposited hydrophobic modified SiO2 aerogel powder is prepared by hydrophobically treating silica aerogel powder with trimethylchlorosilane and hexamethyldisilazane, and then constructing a nano-active deposition layer on its surface using nano-SiO2 sol solution.

2. The method for preparing a foamed silicone thermal insulation material according to claim 1, characterized in that, The foam leveling agent is a polyether-modified silicone oil foam leveling agent; the inhibitor is an alkynyl alcohol inhibitor; and the catalyst is a platinum-based catalyst. The mass ratio of the amounts of alkoxy-functionalized hydrogen-containing silicone oil added before and after the two additions is 1-3:2-5; The foam silicone insulation material comprises the following raw materials in parts by weight: 100 parts by weight of modified vinyl silicone oil, 5-15 parts by weight of hydroxyl silicone oil, 3-8 parts by weight of alkoxy-functionalized hydrogen-containing silicone oil, 5-15 parts by weight of fumed silica, 10-30 parts by weight of nano-deposited hydrophobic modified SiO2 aerogel powder, 4-12 parts by weight of amino-terminated functionalized dimethyl silicone oil, 3-5 parts by weight of dimethyl silicone oil, 1-2.5 parts by weight of foam leveler, 0.05-2 parts by weight of inhibitor, 0.5-3 parts by weight of deionized water, and 0.1-0.5 parts by weight of catalyst.

3. The method for preparing a foamed silicone thermal insulation material according to claim 1, characterized in that, The vulcanization process includes primary vulcanization and secondary vulcanization; The single vulcanization process consists of three stages of gradient vulcanization; the first stage vulcanization temperature is 100-120℃; the second stage vulcanization temperature is 130-150℃; and the third stage vulcanization temperature is 160-180℃; the total vulcanization time for the single vulcanization process is 5-15 minutes. The specific steps of the secondary vulcanization are as follows: secondary vulcanization at 200-230℃ for 2-4 hours; The thickness of the foam silicone insulation material is 0.9-1.1 mm.

4. The method for preparing a foamed silicone thermal insulation material according to claim 1, characterized in that, The preparation method of the modified vinyl silicone oil includes the following steps: under a nitrogen atmosphere, vinyl silicone oil and isopropanol are added to a reaction flask for dispersion, a catalyst is added, the temperature is controlled at 90-100℃, allyl glycidyl ether is added, the reaction is maintained at this temperature for 2-4 hours, allyl amine is added, the reaction is maintained at this temperature for 2-4 hours, and the modified vinyl silicone oil is obtained by vacuum distillation; The catalyst is a platinum-based catalyst; the addition ratio of vinyl silicone oil, isopropanol, catalyst, allyl glycidyl ether, and allylamine is 100g: 100-200mL: 0.01-0.05g: 2-8g: 1-5g.

5. The method for preparing a foamed silicone thermal insulation material according to claim 1, characterized in that, The preparation method of the alkoxy-functionalized hydrogen-containing silicone oil includes the following steps: under a nitrogen atmosphere, hydrogen-containing silicone oil and toluene are added to a reaction flask for dispersion, a catalyst is added, the temperature is controlled at 90-110℃, vinyltriethoxysilane is added, the reaction is kept at the temperature for 4-8 hours, and the reaction is carried out under reduced pressure to obtain alkoxy-functionalized hydrogen-containing silicone oil. The catalyst is a platinum-based catalyst; the addition ratio of hydrogen-containing silicone oil, toluene, catalyst, and vinyltriethoxysilane is 100g: 100-200mL: 0.02-0.08g: 5-15g.

6. The method for preparing a foamed silicone thermal insulation material according to claim 1, characterized in that, The preparation method of the amino-terminated modified dimethyl silicone oil includes the following steps: adding hydroxyl-terminated dimethyl silicone oil and dimethyl silicone oil into a reaction flask for dispersion, controlling the temperature at 60-80℃, adding aminoethylaminopropyldimethoxysilane, keeping the reaction at the temperature for 4-6 hours, and distilling under reduced pressure to obtain amino-terminated modified dimethyl silicone oil. The mass ratio of hydroxyl-terminated dimethyl silicone oil, dimethyl silicone oil, and aminoethylaminopropyl dimethoxysilane is 100:10-30g:5-20g.

7. The method for preparing a foamed silicone thermal insulation material according to claim 1, characterized in that, The preparation method of the nano-deposited hydrophobic modified SiO2 aerogel powder includes the following steps: In a nitrogen atmosphere, silica aerogel powder is added to a closed gas-phase modification reactor and heated to 120-130℃. Trimethylchlorosilane and hexamethyldisilazane are mixed and vaporized. Nitrogen is used as a carrier to introduce the mixture into the gas-phase modification reactor and the reaction is maintained at the temperature for 2-4 hours to obtain trimethylsiloxy hydrophobic grafted modified aerogel powder. Anhydrous ethanol and deionized water were added to a reaction flask and mixed. Dilute hydrochloric acid was added to adjust the pH of the system to 5.0-5.

5. The temperature was controlled at 40-45℃. Tetraethyl orthosilicate was added dropwise. The reaction was kept at the temperature for 3-5 hours under stirring. The temperature was raised to 50-55℃ and kept constant for 1-1.5 hours. The temperature was lowered to room temperature and diluted with anhydrous ethanol to obtain a nano-SiO2 sol solution with a solid content of 11.5-12.5 wt%. The trimethylsiloxy hydrophobic grafted modified aerogel powder prepared above was added to a reaction vessel, and the nano-SiO2 sol prepared above was added. The mixture was stirred and deposited at room temperature for 25-35 min, and the temperature was controlled at 55-65℃ for 0.5-1 h. The mixture was then sieved and dried to obtain nano-deposited hydrophobic modified SiO2 aerogel powder.

8. The method for preparing a foamed silicone thermal insulation material according to claim 7, characterized in that, The silica aerogel powder has a pore size of 10-50 nm and a specific surface area of ​​200-1000 m². 2 / g; The mass ratio of silica aerogel powder, trimethylchlorosilane, and hexamethyldisilazane is 100:5-15:5-15; The dilute hydrochloric acid is a 0.1-0.5 mol / L hydrochloric acid aqueous solution; the addition ratio of anhydrous ethanol, deionized water, and tetraethyl orthosilicate is 180-220 mL: 45-55 mL: 100 g.

9. The method for preparing a foam silicone thermal insulation material according to claim 1, characterized in that, The preparation method of the foam stabilizer includes the following steps: under a nitrogen atmosphere, low-hydrogen silicone oil, octamethylcyclotetrasiloxane, hexamethyldisiloxane and isopropanol are added to a reaction flask and dispersed. A catalyst is added, the temperature is controlled at 90-100℃, allyl polyether is added, the reaction is kept at the temperature for 3-6 hours, and the foam stabilizer is obtained by vacuum distillation. The catalyst is a platinum-based catalyst; the addition ratio of low-hydrogen silicone oil, octamethylcyclotetrasiloxane, hexamethyldisiloxane, isopropanol, catalyst, and allyl polyether is 100g: 20-50g: 5-15g: 100-200mL: 0.02-0.06g: 30-80g.

10. A foamed silicone thermal insulation material, characterized in that, It is prepared by the method described in any one of claims 1-9.